FAKTOR-FAKTOR PENGHAMBAT REVITALISASI PASAR TRADISIONAL DESA TERATAK BULUH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Asep Syahri Romadhan TZ; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
There is a potency that should be viewed good enough to increase the Village Own Source Revenue (PADesa) of Teratak Buluh Village in Siak Hulu subregency of Kampar Regency that is a traditrional market. The establishment of the traditional market began from 2007, nevertheless it stopped in 2012 because of the proposals program of revitalization Teratak Buluh Village Market there is no establishment that accepted from 2012 until 2016 so that the development process of the market does not carried out well. The method that used in this research is descriptive method with qualitative kind analysis. The kind of research data are primary data and secondary data. Analysis data technique used is qualitative descriptive data analysis.The result of this research indicates that the effort of local government to revitalize Teratak Buluh Traditional Market get a decrease. Afterward, to re-increase the development of Teratak Buluh Traditional Market activity, the government of Kampar Regency re-established the traditional market. Began in 2007 until 2011 and in the next year 2012 until 2016 there is no sustainability development of the market. The inhibiting factors of establishment of the Teratak Buluh Traditional Market are the obstacle in Musrenbang Desa Teratak Buluh (The Conference of Development Planning of Teratak Buluh Village) and the second one is the limitation of budget obstacle.Keywords: Establishment, Revitalization, Traditional Market